Optimization of Pandan Leaf Processing (Pandanus Tectorius) as Craft Material: A Comparative Study of Drying and Natural Dyeing Methods - Hani Siti Nurjaihan; Afifah Mu’minah; Andri Pahrulroji (Fakultas Industri Kreatif Universitas Surabaya, 2025)
This research aims to optimize the processing of pandan leaves as craft material through comprehensive analysis of various drying and natural dyeing methods. Nine pandan leaf specimens with different initial treatments were tested using two main drying methods: natural sun-drying and oven drying. The research results show that pandan leaves with dimensions of 4-6 cm width and 40-100 cm length provide an optimal yield rate of approximately 60-70% for high-quality craft material production. The boiling process as initial treatment followed by sun-drying produces the best balance between drying time efficiency, color quality, and material structural integrity. Oven drying for 20 minutes proved equivalent to conventional sun-drying in terms of dryness level, but resulted in brittle material and loss of color absorption capability. Dyeing exploration using turmeric extract, suji leaves, and teak leaves showed that the use of lime water as solvent produces superior color intensity compared to regular water. This research provides significant contribution to the development of standard specifications for sustainable and environmentally friendly pandan leaf craft industry.